Globalization and Social Change: Gender-Specific Effects of Trade Liberalization in Indonesia - Krisztina Kis-Katos; Janneke Pieters; Robert Sparrow (Institute of Labor Economics (IZA), 2017)
We analyse the gender-specific effects of trade liberalization on work participation and hours of work and primary participation in domestic duties in Indonesia. We show that female work participation increased in relative terms in regions that were more exposed to input tariff reductions, whereas the effects of output tariff changes were much less pronounced. When looking at the potential channels for these effects, we find that in Indonesia the structure of initial protection was considerably more female-biased than skill-biased and hence reductions in input tariffs have especially benefited sectors with a larger initial concentration of female workers. This has led to a relative expansion of more female intensive sectors as well as to a decrease in gender segregation of occupation, especially among the low skilled. We also find that labour markets are a key channel through which trade liberalization affects marriage decisions. Delayed marriage among both sexes is related to input tariff liberalization, especially in the younger cohorts, as the improved labour opportunities for women reduce the returns to marriage.
Keywords: F13; F16; J12; J16; J21; 330; labour force participation; gender inequality; marriage; trade liberalization; Indonesia